Management of gag reflex in prosthodontic treatment - Sarwono, Aditya P. (Universitas Sam Ratulangi, 2022)
Abstract: In practice, dentists often find patients with very sensitive oral cavity, which results in patients being unable to tolerate the entry of foreign objects into the oral cavity. Gag reflex can be triggered by any kind of dental procedure both before and after treatment due to various causes. In addition, it can be said that the ability and patience of a dentis are important requirements to be able to control the gag reflex and create a comfortable treatment. This paper is a narrative review consisting of a collection of data on the gag reflex and various treatment methods recorded in the literature. This includes various modifications that dentists and prosthodontists can make during the treatment process such as molding, fabricating, and fitting dentures to treat the patient's gag reflex problem. Although there is no definite solution for the successful management of patients with gag reflex problem, dentists can use various methods to control the gag reflex at their discretion, so that dental treatment can be carried out comfortably.Keywords: gag reflex; prosthodontics; comfortable dental treatmentÂ Abstrak: Dalam praktiknya, sering kali dokter gigi menemukan pasien dengan rongga mulutÂ yang sangat sensitif, yang berakibat pasien tidak dapat mentoleransi masuknya benda asing ke dalam rongga mulut. Refleks muntah dapat dipicu oleh segala jenis prosedur gigi baik sebelum dan sesudah perawatan karena berbagai penyebab. Selain itu, dapat dikatakan bahwa kemampuan dan kesabaran dokter gigi merupakan syarat-syarat penting untuk dapat mengendalikan refleks muntah dan menciptakan perawatan yang nyaman. Studi ini merupakan tinjauan naratif yang terdiri dari kumpulan data mengenai refleks muntah dan berbagai metode penanganannya yang tercatat dalam bentuk literatur. Hal ini mencakup berbagai macam modifikasi yang dapat dilakukan oleh dokter gigi maupun prostodontis selama proses perawatan seperti pencetakan, pembuatan dan pemasangan gigi palsu untuk menangani masalah refleks muntah pasien. Meskipun tidak ada solusi yang pasti untuk keberhasilan manajemen pasien dengan masalah refleks muntah, dokter gigi dapat meng-gunakan berbagai macam metode untuk mengontrol refleks muntah sesuai pertimbangannya sendiri sehingga perawatan gigi dapat dilakukan dengan nyaman.Kata kunci: refleks muntah; kedokteran gigi; prostodonti; perawatan gigi yang nyaman